2022
DOI: 10.48208/headachemed.2022.23
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors of migraine headache among university students: A cross-sectional study in Lebanon

Abstract: Background Migraine constitutes a major public health concern since it negatively affects both the quality of life and the productivity of patients. Migraine among students can cause impaired academic performance and limit their daily activities. Objective This study aims to assess the prevalence of migraine among university students using the ID Migraine screening tool and to evaluate risk factors associated with migraine. Methods A cross-sectional study was performed over a period of six months targeting 114… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 33 publications
0
1
0
Order By: Relevance
“…31 The majority of migraine sufferers had a family history of chronic headache. Our results were close to those of Raju et al 23 in India (49%) and Hatem et al, 32 (41%). In contrast, lower prevalence of family history of migraine was present in the study of Adoukonou33 in Benin (14.6%) and in a study conducted in India (20.1%).34 The relative risk of migraine for a first-degree relative of an index case was 1.5-to 4-fold compared with the general population.…”
Section: Migraine Frequencysupporting
confidence: 91%
“…31 The majority of migraine sufferers had a family history of chronic headache. Our results were close to those of Raju et al 23 in India (49%) and Hatem et al, 32 (41%). In contrast, lower prevalence of family history of migraine was present in the study of Adoukonou33 in Benin (14.6%) and in a study conducted in India (20.1%).34 The relative risk of migraine for a first-degree relative of an index case was 1.5-to 4-fold compared with the general population.…”
Section: Migraine Frequencysupporting
confidence: 91%
“…In Kuwait, 27.9% of medical students were suggested to have migraines based on the ID-Migraine™, a rate that is quite similar to the higher end of prevalence in Saudi Arabia [ 24 ]. These comparisons reveal that while migraines are a common concern among medical students globally, the extent of their impact varies significantly from one region to another.…”
Section: Reviewmentioning
confidence: 99%
“…20 Most recently, a study revealed that 35.8% of university students had migraine with a higher prevalence among women. 21 In order to maximize students' awareness of migraine attacks, migraine management must be improved by identifying and avoiding common trigger factors. 22 Moreover, assessing the factors that relieve headaches can improve their quality of life and productivity by reducing the magnitude of disabilities related to migraine.…”
Section: Introductionmentioning
confidence: 99%